2014
DOI: 10.1002/cjce.22008
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent couette flow between corrugated walls: The case with motion of one wall perpendicular to the corrugation cavities

Abstract: In this work, we numerically examine the two dimensional flow of a Newtonian fluid in the gap formed between two opposing cavities. The fluid is driven by the motion of the upper cavity and the case considered represents a simplified version of the geometry found in Low Consistency (LC) refiners. Numerical studies were conducted in which we characterized the effect of gap size on the flow field. Then, we examine material transport between the cavities by introducing a passive scalar to represent the motion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Literature in this research area is very limited; to our best knowledge, the disc refining process modeling based on fundamental mechanics in energy consumption prediction has not been reported for either pulping or biorefinery applications. However, a few researchers have been developing computational fluid dynamics (CFD) models to understand the low-consistency pulping process in disc refiners. The computational domain is usually simplified to reduce computational complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature in this research area is very limited; to our best knowledge, the disc refining process modeling based on fundamental mechanics in energy consumption prediction has not been reported for either pulping or biorefinery applications. However, a few researchers have been developing computational fluid dynamics (CFD) models to understand the low-consistency pulping process in disc refiners. The computational domain is usually simplified to reduce computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…The computational domain is usually simplified to reduce computational complexity. Some works , reported two-dimensional geometry for disc refining modeling, while others , believe that the three-dimensional (3D) flow characteristics are critical in modeling the disc refining process. While the reported studies use simplified geometries for disc refiner plates, we believe that using 3D, high-fidelity refiner plate geometry is critical to correctly predict the flow behavior and energy consumption in the disc refining process.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the results of the Newtonian model in their study are close to that of the non-Newtonian model based on the experimental measurements of Ventura et al. 13 A simplified model of an LC refiner is considered in Nasab et al 14 assuming a Newtonian turbulent flow in a two-dimensional geometry. The grooves geometry in their study comprised of two opposing cavities in which the flow was driven by the movement of the upper cavity.…”
Section: Introductionmentioning
confidence: 55%